Cyanide Contents in Pits of Cherries, Gages and Plums Using a Modified Sensitive Picrate Method - Grgurič, Luka; Kraner Šumenjak, Tadeja; Kristl, Janja (Agricultura Scientia, 2022)
Cyanogenic glycosides are present in at least 2500 taxonomic groups of different plant families, including many economically important fruit species. They are most concentrated in the seeds of fruits and may pose a risk to human health due to the release of cyanide. In the present study, we compared the cyanide content in the pits of cherries (Prunus avium L.), plums (Prunus domestica L.), and gages (Prunus domestica subsp. italica (Borkh.) Gams) using the picrate paper method. The lowest cyanide content (19.6 μg/g) was found in a cherry accession (R x L 98), and the highest (310 μg/g) in a gage accession (Gage 6319). Considerable variation in cyanide content was found within varieties of a fruit tree species, reaching a coefficient of variation of 56.9% for cherries, 54.4% for plums, and 30.5% for gages. Looking at the overall medians, the results show that the cyanide content in the pits of gages was significantly higher than the cyanide content in the pits of plums and cherries.
Keywords: cyanide; pits; cherries; gages; plums